2006
DOI: 10.1002/pola.21427
|View full text |Cite
|
Sign up to set email alerts
|

Novel organosoluble and colorless poly(ether imide)s based on 3,3‐bis[4‐(3,4‐dicarboxyphenoxy)phenyl]phthalide dianhydride and aromatic bis(ether amine)s bearing pendent trifluoromethyl groups

Abstract: A novel series of colorless and highly organosoluble poly(ether imide)s were prepared from 3,3-bis [4-(3,4-dicarboxyphenoxy)phenyl]phthalide dianhydride with various fluorinated aromatic bis(ether amine)s via a conventional two-stage process that included ring-opening polyaddition to form the poly(amic acid)s followed by cyclodehydration to produce the polymer films. The poly(ether imide)s showed excellent solubility, with most of them dissoluble at a concentration of 10 wt % in amide polar solvents, in ether-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…It is sharply contrasted with the typical aromatic polyimide film derived from PMDA and ODA, which showed deep yellow color and exhibited λ 0 of 445 nm and transmittance at 450 nm of 2%. The excellent optical transparency of these films was attributed to the incorporation of the bulky cardo phthalide groups in the polymer structure, which inhibited close packing, thereby increasing the free volume among the molecular chains and suppressing the inter-and intramolecular charge transfer interactions effectively [27,28]. As comparing the coloration of these films, it is interestingly observed that optical transparency slightly increased with decreasing the content of phthalimide unit in the polymer backbone.…”
Section: Optical Propertiesmentioning
confidence: 91%
See 3 more Smart Citations
“…It is sharply contrasted with the typical aromatic polyimide film derived from PMDA and ODA, which showed deep yellow color and exhibited λ 0 of 445 nm and transmittance at 450 nm of 2%. The excellent optical transparency of these films was attributed to the incorporation of the bulky cardo phthalide groups in the polymer structure, which inhibited close packing, thereby increasing the free volume among the molecular chains and suppressing the inter-and intramolecular charge transfer interactions effectively [27,28]. As comparing the coloration of these films, it is interestingly observed that optical transparency slightly increased with decreasing the content of phthalimide unit in the polymer backbone.…”
Section: Optical Propertiesmentioning
confidence: 91%
“…The PEKI-C films about 20 µm thick exhibited good mechanical properties with tensile strengths of about 100 MPa, elongations at break of more than 9.7 %, and tensile moduli of more than 2.2 GPa. It is noted that the tensile strengths, elongations at break, and tensile moduli increased with increasing the content of the phthalimide unit, which effectively contributed to the inter-chain interactions [27,28].…”
Section: Mechanical Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…The solubility and thermal characteristics of the polymers can be enhanced by having cyclic side groups, such as fluorene, phthalide, and phthalimidine groups on the polymer backbone [6][7][8]. Thus, the introduction of phthalimide groups into the macromolecular chains of polyhydrazides improves the properties of the resulting materials.…”
mentioning
confidence: 99%